2001
DOI: 10.1002/j.2161-0045.2001.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Practice and Research in Career Counseling and Development—2000

Abstract: The authors summarize the career counseling and development literature that appeared during 2000 in refereed journals, book chapters, and full-length books. The review of literature is divided into 5 major categories: (a) theoretical and conceptual advances, (b) career counseling and development ofidentified populations, (c) assessment in career counseling and development, (d) career counseling programs and interventions, and (e) resources for the professional development of career counselors and vocational ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 179 publications
0
13
0
6
Order By: Relevance
“…Furthermore, the most recent reviews (e.g., Arbona, 2000;Luzzo & MacGregor, 2001;Whiston & Brecheisen, 2002) have noted a trend of increased multicultural career development research. The research published in 2002 continues to attend to the career development of women and people from diverse racial and ethnic backgrounds, including African Americans, Latinas and Latinos, and Asian Americans.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the most recent reviews (e.g., Arbona, 2000;Luzzo & MacGregor, 2001;Whiston & Brecheisen, 2002) have noted a trend of increased multicultural career development research. The research published in 2002 continues to attend to the career development of women and people from diverse racial and ethnic backgrounds, including African Americans, Latinas and Latinos, and Asian Americans.…”
Section: Discussionmentioning
confidence: 98%
“…The number of articles and journals represented in the reviews has grown over time. Each one of those 25 reviews provided a brief summary of the content of articles by topic, as well as a commentary on the nature of the literature published that year (Arbona, 2000;Bikos, Dykhouse, Boutin, Gowen, & Rodney, 2013;Chope, 2008;Cook, 1991;Creager, 2011;Dagley & Salter, 2004;Erford & Crockett, 2012;Flores et al, 2003;Guindon & Richmond, 2005;Harrington & Harrigan, 2006;Hartung, 2010;Jepsen, 1992;Luzzo & MacGregor, 2001;Niles, 1997;Patton & McIlveen, 2009;Salomone, 1993;Savickas, 1989;Spokane & Hawks, 1990;Stoltz-Loike, 1996;Subich, 1994;Swanson & Parcover, 1998;Tien, 2007;Walsh & Srsic, 1995;Whiston & Brecheisen, 2002;Young & Chen, 1999). In reviewing past CDQ annual reviews, we identified some noteworthy trends.…”
mentioning
confidence: 99%
“…A significant aspect of career counseling is helping customers define personal expectations and goals in relation to who and what they are: their own background, developmental issues, interests, previous careerrelated experiences, and career opportunities (Axelson, 1999;Gysbers, Heppner, & Johnston, 2003;Hartung et al, 1998;Herr, Cramer, & Niles, 2004;Luzzo & MacGregor, 2001). Career counseling helps customers to identify, develop, and use resources that allow them to expand opportunities and choices they perceive as being available in their environment (Axelson, 1999;Constantine, Wallace, & Kindaichi, 2005;Richie et al, 1997).…”
Section: University Of Kentuckymentioning
confidence: 99%